PERTUMBUHAN DAN HASIL BEBERAPA GENOTIPE TANAMAN PADI (Oryza sativa L.) PADA BERBAGAI METODE TANAM - Holil, Maskur; Dulbari, Dulbari; Priyadi, Priyadi; Rochman, Fajar; Subarjo, Subarjo (Universitas Lampung, 2025)
Optimal rice production is very important to meet national food needs amid a decline in harvest area and production yields. This study aims to analyze the influence of rice planting methods and genotype on the growth and yield of rice plants (Oryza sativa L.). The research was conducted on the Lampung State Polytechnic Experimental Land using a factorial Group Random Design (RAK) with two factors: the planting method (legowo row 2:1, planting distance 25x25 cm, and transplanter 2:1) and rice genotype (PTP 01, Inpari 24, Jeliteng, and Pandan Wangi) each method was repeated 3 times. The results of the study show that the interaction of planting methods and rice genotype has a significant effect on the growth and yield of rice plants. The combination of the 2:1 transplanter planting method and the Inpari 24 genotype gave the best results in terms of plant height (101.33 cm), number of saplings (29.33), number of productive saplings (25.00), and yield per hectare (12.48 tons/ha). The 2:1 transplanter planting method and the Inpari 24 genotype can be recommended as the best combination in increasing rice productivity.